American Students’ Cultural Adjustment in China: Experiences and Coping Strategies - Yang, Jia (Journal of International Students, 2020)
Employing critical incident technique and the constructivist grounded approach, this study conducted individual in-depth interviews with 13 undergraduate students who had experiences studying abroad in China to find out how American college students perceived their new learning environment in China, and to examine the strategies students employed to adjust to the new culture. The results provided practical suggestions for the design and implementation of study abroad programs in China, including the compatibility between the program structure and individual student’s learning needs and aspirations, the use of service-based community-building activities to foster the mutual engagement in interactions between American students and host nationals, and the inclusiveness of local perspectives in American students’ reflection of their cultural immersion experiences.